Review. (1st April 2013) - Goodman, Joshua
The Routledge History of Social Protest in Popular Music, Jonathan C. Friedman (ed.) (2013) New York and Abingdon: Routledge, 414 pp., ISBN: 9780415509527, h/bk, £140.00